Environmental ethical awareness of solid waste management - ดวงจันทร์ เกียรติศักดิ์ (Journal of Liberal Arts Prince of Songkla University, 2018)
This research aimed to investigate 1) the context, problems and environmental ethical awareness of solid waste management in the community; 2) a relationship between ethical awareness of the environment and solid waste management; and 3) to develop guidelines to raise public awareness of waste disposal. The study was conducted in Wat Pradu Sub-district Municipality, Mueang District, Surat Thani Province. Questionnaires and interviews were used as research instruments. Data were collected from 380 copies of questionnaire and interviews with 30 key informants including community leaders, business leaders and waste management officers. Means, standard deviation, Pearson correlation coefficient and inductive content analysis were used to analyze the data. The research findings revealed that 1) the study results of the context, problems and environmental ethical awareness of solid waste management showed that, through social, political, and economic changes, Wat Pradu Sub-district had been expanded into three phases; a traditional community, an inner-city community, and a new housing development community. Most of the residents had knowledge and awareness of direct and indirect impacts of waste on the environment and health. 2) With respect to a relationship between ethical awareness of the environment and waste management, it was found that the residents had a relatively high level of awareness of the environment and a high level of awareness of waste management. A detailed investigation of different aspects of waste management found that management of waste reduction and reuse were satisfactory while management of solid waste disposal, recycling and upcycling were at moderate levels. It was also found that environmental ethical awareness had a positive correlation with solid waste disposal with statistical significance at 0.01, and 3) It is suggested that a sufficient number of public litter bins and waste sorting bins, promotion of environmentally friendly materials, additional support for waste recycling businesses and environmental awareness activities will promote ethical awareness of the community.